Otitis media with effusion and hearing loss in childen with orofactial clefts. (2019)
Background: Little or no attention is given to hearing health of children with orofacial cleft. This study was carried out to determine the prevalence of otitis media with effusion (OME) and evaluate hearing thresholds of children with orofacial cleft in Nigeria. Methodology: Eighty-three consecutive children with orofacial cleft comprising, 12 (14.5%) cleft lip alone, 32 (38.5%) cleft lip and palate and 39 (47.0%) cleft palate alone, and 83 healthy controls participated in the study. Structured questionnaire was used to collect socio-demographic and relevant medical information. Participants had ear, nose and throat examinations, visual reinforcement or condition play audiometry and tympanometry tests done. Statistical analysis was done with appropriate statistical tools, level of significance was set at p<0.05. Results: Mean age of cases was 22.83 ± 2.71 months and controls was 23.34 ± 2.54 months. Hearing loss was found in 28 (16.9%) ears of cases and 14 (8.5%) ears of controls (p=0.021). There was a significant difference between mean hearing thresholds of cleft palate ± lip and control (p<0.05). OME was present in 80 (48.2%) ears of cases and 17 (10.2%) ears of the controls (p=0.001). There was a statistically significant association between cleft palate ± lip and OME (p=0.0001, OR = 4.520 [2.353-8.681]). Conclusion: Otitis media with effusion and hearing loss were more prevalent among children with orofacial cleft palate than non-cleft children. Hence, routine early hearing and middle ear evaluations are recommended for inclusion in their management plan.